Peer Interactions of Preschool Children With and Without Hearing Loss. - DeLuzio, Joanne; Girolametto, Luigi (Journal of Speech, Language & Hearing Research, 2011)
Purpose: Little is known about the social interaction skills of children with severe to profound hearing loss (SPHL) in terms of how they manage conversational exchanges with peers. This study compared the initiation and response skills of children with SPHL with those of children with typical hearing during group play in integrated preschool programs. Method: Two groups of 12 children were matched on a number of variables and assessed for intelligence, language, speech, and social development. All initiations, responses, and resulting interactions during 20 min of group play were transcribed and coded. Outcome measures included number and type of initiation strategies, number of responses, and length of interactions. Results: Despite poorer speech, language, and social development, there were no significant differences in initiation and response skills measured between children with SPHL and their matched peers. The small sample size may have made differences difficult to detect; however, playmates initiated interactions less often with the children with SPHL and ignored their initiations more often than those of other children. Conclusions: Preschool children with SPHL were excluded from interactions by their playmates. Having age-appropriate language skills did not ensure successful peer interactions. Inclusive preschool programs may consider offering classroom-wide social skills training to enhance interaction opportunities. Reprinted by permission of the publisher.